HUBUNGAN MODAL SOSIAL DAN MODAL MANUSIA DENGAN TINGKAT PENDAPATAN PETANI KARET DI KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR - Hakim, Nukmal; Malini, Henny; Oktarina, Selly (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2010)
Relationship of Social Capital and Human Capital with rubber Farmer Income in the District of Tanjung Batu Ogan Ilir, the purpose of this study is to analyze how much Social Capital and Human Capital owned rubber farmers and farmer income Counting Rubber, and analyze the relationship between human capital and social capital Rubber farmers with income and identify the efforts made by rubber farmers in the district of Tanjung Batu in Ogan Ilir enhance Social Capital and Human Capital. The research method used in this study is a survey method. Social capital is owned by farmers in the village of Tanjung Batu rubber is set at 45.57 which is in the criteria are and Human Capital owned by farmer rubber is set at 14.36 which is also located on the stage or the criteria are. Average farm incomes rubber rubber farmers in the village of Tanjung Batu this is Rp. 32,305,181.41 per hectare per year and an average total income 35,051,848.07 per year. Correlation test by using Spearman correlation test showed that there is no relationship between social capital rubber farmers with incomes of farmers in the village of Tanjung Batu Tanjung Batu subdistrict Ogan Ilir, meaning that the higher the social capital of farmers will not affect farmers' income so anything and vice versa. Correlation test using Sperarman correlation test also showed that there was no relationship between the human capital with income levels of rubber farmers in the village of Tanjung Batu Ogan Ilir. Efforts being made to increase social capital by increasing social interaction with the local environmental community and the outside environment so that it will obtain useful inputs and efforts to enhance human capital is to diligently follow the training and the courses that are useful for their lives, always maintain personal hygiene and the environment.